PENERAPAN PENDEKATAN PEMBELAJARAN STEM TERHADAP PEMAHAMAN KONSEP IPA SISWA KELAS V SDN TIDUNG - Mahirah; Nurlina; Hilmi Hambali (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The main problem in this study is that students' understanding of science concepts is still relatively low. This study aims to analyze students' conceptual understanding before the STEM learning approach is implemented, to analyze students' conceptual understanding after the STEM learning approach is implemented, and to analyze the increase in students' knowledge before and after the STEM learning approach is implemented. This study was a pre-experimental study involving one class as the focus class using a One Group Pretest-Posttest Design. The population was 26 fifth-grade students at Tidung Elementary School. Data collection involved distributing science test sheets to measure student learning outcomes before and after using the STEM approach, along with observation sheets. The results showed that the average pretest score was 51.54, categorized as low and incomplete, while after implementing the STEM learning approach, the average posttest score was 80.39, categorized as high and complete. The N-gain test showed an average student score of 0.62, which falls into the moderate category. Therefore, it can be concluded that the application of the STEM learning approach has improved the understanding of fifth-grade students' science concepts at Tidung Elementary School.